KEMAMPUAN KOAGULAN KITOSAN DENGAN VARIASI DOSIS DALAM MENURUNKAN KANDUNGAN COD DAN KEKERUHAN PADA LIMBAH CAIR LAUNDRY (Studi pada Rahma Laundry, Kecamatan Tembalang, Kota Semarang) - Dyah Agustin Catur Putri; Tri Joko; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Laundry liquid waste contains several chemical substances in detergent raw materials such as phosphate, surfactants, ammonia, and total suspended solids. The existence of detergent in high concentrations and exceeds the quality standards that have been estabilished in a body of water can lead to cases of enviromental pollution in the form of increased turbidity an Chemical Oxygen Demands (COD) levels. Therefore in order to maintain and to ensure the availabillity of water in terms of quality, it requires coagulation-flocculation process to laundry liquid waste before discharging into water bodies. This study aims to determine the decrease of COD levels and turbidity level in laundry liquid waste using chitosan coagulant in Rahma Laundry, Tembalang District, Semarang. The research is a quasi experimental study with pretest-posttest with control group research design with 6 times replication. The total samples are 60 in wich 24 tested for the levels of turbidity and 6 controls. The test results of Kruskal-Wallis with significance p-value < 0,05 indicates that dosage variation (p=0,000) gives different levels of COD and dosage variation (p=0,000) provide 755,97 mg/l and the advantage levels of turbidity before treatment was 516,20 NTU. The optimum dosage of chitosan coagulant is on the dose of 200 mg/l with the effectiveness decrease of COD levels and turbidity levels on 72,67% an 98,67% respectively.